ANALISIS PENENTUAN HARGA POKOK PRODUKSI, NILAI TAMBAH DAN STRATEGI OPERASIONAL AGROINDUSTRI KOPI LAMPUNG SR DI KOTA BANDAR LAMPUNG - Nadya Kurnia Sari; Yaktiworo Indriani; Lina Marlina (Lampung University, 2022)
This study aims to analyze the cost of production, added value, internal and external factors and operational strategies of Lampung SR Coffee Agroindustry. This research is a case study involving respondents of agroindustry owners, employees, and consumers and addition to lecturers of agribusiness and employees at the Department of Industry and Trade of Lampung Province. The data was analyzed quantitative descriptively by cost of goods manufactured and added value and qualitative descriptively by SWOT analysis . The result showed that the production cost of Lampung SR Coffee Agroindustry was IDR45,938/kg to IDR106,856/kg. The added value generated was IDR17,241.75/kg – IDR103,385.89/kg. After knowing the total value of internal factors and externals factor, it was known that the agroindustry was in quadrant I (growth). The strategy that might be implemented was to expand the marketing areas, increase production and carry out by online marketing using promotion and business development by utilizing its strengths. Key words : added value, agroindustry, operational strategy, production cost